2020
DOI: 10.1021/acsomega.9b03835
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Based Mixed Phosphate Na4Fe3(PO4)2P2O7 Thin Films for Sodium-Ion Microbatteries

Abstract: Iron-based polyanionic materials can be exploited to realize low cost, durable, and safe cathodes for both bulk and thin film sodium-ion batteries. Herein, we report pulsed laser deposited mixed phosphate Na4Fe3(PO4)2P2O7 as a positive electrode for thin film sodium-ion microbatteries. The bulk material and thin films of Na4Fe3(PO4)2P2O7 are employed by solution combustion synthesis (SCS) and the pulsed laser deposition (PLD) technique, respectively. Phase purity and the nature of the crystallinity of the thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Furthermore, it exhibited remarkable electrochemical performance comparable to those of bulk batteries, with a reversible capacity of about 118 mA g -1 at room temperature and about 110 mAh g -1 even at a current density of 10 µA cm -2 . [173] Boyadzhieva et al found that Na 4−x Fe 3 (PO 4 ) 2 P 2 O 7 /C composite allowed for reversible intercalation of both Na + and Li + , and the imide-based electrolyte salts LiTFSI and NaTFSI in organic electrolytes were more favorable for alkali ions to inset into different crystal positions in Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) compared with traditional LiPF 6 and NaPF 6 salts (Figure 8i). [174] Like other polyanion-type cathode materials, Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) also suffers from slow kinetic and poor conductivity.…”
Section: Sodium Iron Phosphate-pyrophosphatementioning
confidence: 99%
“…Furthermore, it exhibited remarkable electrochemical performance comparable to those of bulk batteries, with a reversible capacity of about 118 mA g -1 at room temperature and about 110 mAh g -1 even at a current density of 10 µA cm -2 . [173] Boyadzhieva et al found that Na 4−x Fe 3 (PO 4 ) 2 P 2 O 7 /C composite allowed for reversible intercalation of both Na + and Li + , and the imide-based electrolyte salts LiTFSI and NaTFSI in organic electrolytes were more favorable for alkali ions to inset into different crystal positions in Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) compared with traditional LiPF 6 and NaPF 6 salts (Figure 8i). [174] Like other polyanion-type cathode materials, Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) also suffers from slow kinetic and poor conductivity.…”
Section: Sodium Iron Phosphate-pyrophosphatementioning
confidence: 99%
“…Graphene coated NFPP particles with spherical morphology delivers 128 mAh/g of discharge capacity at 0.1°C and very long cycling stability up to 6000 cycles at 10 C rate with 62.3% capacity retention (Yuan et al, 2019). Interestingly, the thin films of Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 displayed highly reversible Na + storage capacity of 120 mAh/g at 1 C rate with stable cycle life of 500 cycles (Senthilkumar et al, 2020). On the other hand, the Na 4 Mn 3 (PO 4 ) 2 P 2 O 7 exhibits large potential Mn 2+ /Mn 3+ redox couple (3.84 V) and delivers 121 mAh/g of reversible capacity at C/20 rate.…”
Section: Phosphate Cathode Materialsmentioning
confidence: 99%
“…Graphene coated NFPP particles with spherical morphology delivers 128 mAh/g of discharge capacity at 0.1 C and very long cycling stability up to 6000 cycles at 10 C rate with 62.3% capacity retention (Yuan et al, 2019). Interestingly, the thin films of Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 displayed highly reversible Na + storage capacity of 120 mAh/g at 1 C rate with stable cycle life of 500 cycles (Senthilkumar et al, 2020 /C-CNTs microsphere with superior electronic and ionic conductivity, which shows 96.1 mAh/g of first reversible capacity with 371 Wh/kg of energy density at 0.1 C and 3.86 V of operating potential. Figure 12(b) shows the effect of CNT, which displays high specific capacity at each rate.…”
Section: Mixed Pyrophosphatesmentioning
confidence: 99%
“…All synthetic methods include several intermediate steps comprising stirring, drying, grinding, and/or pelletizing. , Even in this case, the obtained NFPP usually contains admixtures such as maricite-type NaFePO 4 and Na 2 FeP 2 O 7 . Recently, Barpanda et al have demonstrated the formation of NFPP thin films by pulsed laser deposition for sodium-ion microbatteries . Irrespective of the developed methods of synthesis, the optimal morphology and composition of NFPP in regard to its electrochemical properties are still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that has an impact on the storage performance of alkali-ion batteries is the electrolyte composition encompassing both the electrolyte salt and solvent. Till now, several sodium, lithium, and potassium salts in organic-based electrolytes have been tested and reported for NFPP: 1 M NaClO 4 in propylene carbonate (PC) , (with 2 vol % fluoroethylene carbonate (FEC)), 1 M NaClO 4 in ethylene carbonate (EC)/diethyl carbonate (DEC)/FEC, 1 M NaClO 4 in EC/PC (with 5 vol % FEC), 1 M NaPF 6 in EC/DEC, and 0.8 M KPF 6 in EC/DEC . The aqueous electrolytes have also been studied, and a high-concentrated solution of NaClO 4 is proposed as an effective and low-cost electrolyte for constructing a high-performance aqueous cell .…”
Section: Introductionmentioning
confidence: 99%